Physical Chemical Characteristics of Crackers with the Addition of Catfish Bone Paste (Clarias sp) and White Oyster Mushroom Flour (Pleurotus ostreatus) - Nurlaela, Raden Siti; Handayasari, Faridah; Kusumaningrum, Intan; Handayani, Delis (Program Studi Teknologi Pangan, 2024)
Crackers are a food made from tapioca where the nutritional content, such as protein, is still low. This research aims to study and analyze the effect of adding catfish bone paste and white oyster mushroom flour on the physicochemical properties and determine the selected product. The research design used was a one-factor Completely Randomized Design (CRD), namely the comparison of the addition of catfish bone paste and white oyster mushroom flour with six treatment levels, namely (0% : 0%), (5%: 25%), (10%: 20%), (15%: 15%), (20%: 10%), and (25%: 5%). Data analysis used Analysis of Variance (ANOVA) followed by Duncan's test with a 95% confidence interval. The analysis used is physical and chemical analysis, namely efflorescence, water content, ash content, acid insoluble ash content, protein content, and calcium content. The results of the physical and chemical test analysis of catfish bone paste crackers with the addition of white oyster mushroom flour are that the efflorescence ranges between 227.793 - 384.567%, the water content ranges from 4.76-6.53%, the ash content ranges from 1.15-7.07 %, acid insoluble ash content ranges from 0.19-0.28%, protein content ranges from 1.66-11.77% and calcium content ranges from between 0.46-3.72%. The selected crackers with the addition of 20% catfish bone paste and 10% white oyster mushroom flour had an efflorescence of 311.592%, water content of 5.79%, a total ash content of 6.42%, an acid insoluble ash content of 0.27%, protein content 7.46% and calcium content 3.24%.